Body composition in amyotrophic lateral sclerosis subjects and its effect on disease progression and survival. Issue 5 (2nd February 2022) - Tandan, Rup; Levy, Evan A; Howard, Diantha B; Hiser, John; Kokinda, Nathan; Dey, Swatee; Kasarskis, Edward J
ABSTRACT: Background: Motor neuron degeneration and malnutrition alter body composition in amyotrophic lateral sclerosis (ALS). Resulting losses of weight, fat mass (FM), and fat-free mass (FFM) shorten survival. Nutritional management relies on body weight or BMI; neither reliably indicates malnutrition nor differentiates body compartments. Objectives: We aimed to 1 ) develop an equation to compute FM and FFM using clinical data, validated against DXA; and 2 ) examine the effect of computed FM and FFM on disease course and survival. Methods: We studied 364 ALS patients from 3 cohorts. In Cohort #1 we used logistic regression on clinical and demographic data to create an equation (test cohort). In Cohort #2 we validated FM and FFM computed using this equation against DXA (validation cohort). In Cohort #3, we examined the effect of computed body composition on disease course and survival. Results: In Cohort #1 ( n = 29) the model incorporated sex, age, BMI, and bulbar-onset to create an equation to estimate body fat: % body fat = 1.73 – [19.80*gender (1 if male or 0 if female)] + [0.25*weight (kg)] + [0.95*BMI (kg/m 2 )] − (5.20*1 if bulbar-onset or *0 if limb-onset). In Cohort #2 ( n = 104), body composition using this equation, compared to other published equations, showed the least variance from DXA values. In Cohort #3 ( n = 314), loss of body composition over 6 mo was greater in males. Adjusted survival was predicted by low baseline FM (HR: 1.39; 95% CI: 1.07, 1.80), and loss of FM (HR: 1.87; 95% CI: 1.30, 2.69) and FFM (HR: 1.73; 95% CI: 1.20, 2.49) over 6 mo. Conclusions: Our equation broadens the traditional nutritional evaluation in clinics and reliably estimates body composition. Measuring body composition could target FM as a focus for nutritional management to ensure adequate energy intake and complement measures, such as the ALS functional rating scale-revised score and forced vital capacity, currently used. Graphical Abstract: